1996
DOI: 10.1021/ic960259b
|View full text |Cite
|
Sign up to set email alerts
|

Near-IR FT-Raman Spectroscopy of Methyl-B12 and Other Cobalamins and of Imidazole and Imidazolate Methylcobinamide Derivatives in Aqueous Solution

Abstract: Near-IR FT-Raman spectra of B12 imidazole derivatives and cobalamins in aqueous solution were compared since there is now strong evidence that, in human B12-dependent enzymes, the 5,6-dimethylbenzimidazole (DMBz) is replaced by imidazole from a histidine in the protein. Derivatives studied include methylcobalamin [MeCbl (DMBz base-on) and MeCbl+ (base-off by acidification to protonate the DMBz)], methylaquacobinamide (MeCbi+) [Cbi's have the DMBz-bearing nucleotide loop removed by hydrolysis], and Me(N-acetylh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
58
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 34 publications
10
58
0
Order By: Relevance
“…The fact that a vibrational mode showing strong enhancement upon laser excitation into the “α-band” is sensitive to isotopic labeling at C10 implies that significant coupling occurs between corrin SA-stretching motion and an LA-polarized electronic transition. Although it had generally been assumed that the corrin-centered vibrational modes mainly involving SA-stretching motion should only couple to SA-polarized electronic transitions, 45,46 our recent DFT-based rR intensity calculations revealed that these modes can in fact also couple to LA-polarized electronic transitions. 48 …”
Section: Results and Analysismentioning
confidence: 82%
See 2 more Smart Citations
“…The fact that a vibrational mode showing strong enhancement upon laser excitation into the “α-band” is sensitive to isotopic labeling at C10 implies that significant coupling occurs between corrin SA-stretching motion and an LA-polarized electronic transition. Although it had generally been assumed that the corrin-centered vibrational modes mainly involving SA-stretching motion should only couple to SA-polarized electronic transitions, 45,46 our recent DFT-based rR intensity calculations revealed that these modes can in fact also couple to LA-polarized electronic transitions. 48 …”
Section: Results and Analysismentioning
confidence: 82%
“…On the basis of these findings, the ~1500 and ~1550 cm −1 features were assigned as vibrational modes that primarily entail stretching motion of the conjugated C–C and C–N bonds oriented along the LA (the LA-stretching mode) and the SA (the SA-stretching mode), respectively. 45,46 In support of these assignments, the ~1550 cm −1 feature was shown to undergo a significant down-shift upon H/D exchange at C10, while the ~1500 cm −1 feature was largely unaffected by this isotopic substitution. 45 However, on the basis of a density functional theory (DFT)-assisted normal mode analysis for methylcobalamin (MeCbl), 47 Kozlowski and coworkers suggested that the frequency of the SA-stretching mode is in fact lower than that of the LA-stretching mode.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…20 Model studies and theoretical calculations also show that displacement of α-DMB trans to an alkyl ligand by imidazole-type ligands does not significantly increase the rate of homolytic cleavage or decrease the bond strength of the Co-C bond. [21][22][23][24] Furthermore, although initial X-ray diffraction results suggested that the Co-N(Im) bond is abnormally long for some B 12 -dependent enzymes (2.5 Å for MCM 7 and 2.3 Å for glutamate mutase 10 ), the structures may actually represent Co in mixed-ligand and oxidation states (Co III and Co II ), due to X-ray-induced photoreduction. 10,[25][26][27] In protein-free Cbls, α-DMB is difficult to displace from the α-axial site but can be displaced by cyanide, 28 by imidazole-type ligands, 29,30 and by protonation of the basic N of the imidazole moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Model studies have shown that a weaker donor ligand causes the carbon-cobalt bond to become longer and the bond dissociation energy to decrease (15)(16)(17). In contrast, FT-Raman (18) and resonance Raman (19) studies have shown that, for alkylcobalamins, carbon-cobalt bond stretching frequencies do not depend on the trans axial ligand. Thus the role of the axial ligand is more complex than simply modulation of the carbon-cobalt bond strength.…”
mentioning
confidence: 99%